2020
DOI: 10.1111/bjd.19057
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated E3 ligase tripartite motif‐containing protein 21 in psoriatic epidermis ubiquitylates nuclear factor‐κB p65 subunit and promotes inflammation in keratinocytes*

Abstract: Summary Background Tripartite motif‐containing protein 21 (Trim21) is an E3 ubiquitin‐protein ligase that plays pivotal roles in various diseases. However, its role in mediating keratinocyte inflammation, which is a hallmark of psoriasis, has not been thoroughly elucidated. Objectives To clarify whether Trim21 plays a pivotal role in regulating keratinocyte inflammation in psoriasis, while focusing on identifying key Trim21 substrates involved in mediating proinflammatory cytokine and chemokine production. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…All these proteins were downregulated, indicating coagulation dysfunction.Signaling pathways are important for VI induced by MGX, as previous research has reported that MGX directly activates the NF-κB signaling pathway via the MAPK pathway (protein accession number: P62987; FC = 5.17)[41]. Our study shows that protein accession number P19474 is a biomarker or drug target, as trim21 upregulation (FC = 1.62) can improve keratinocyte in ammation by activating the NF-κB pathway[49]. According to GO analysis and KEGG pathway annotation and enrichment, our study is the rst to show that the Wnt, ERBB, and BMP signaling pathways are also important for VI induced by MGX; however, the mechanism by which MGX contributes to the pathogenesis of VI through signaling pathways remains unclear.Up-or downregulation of the following proteins (Table2) was closely related to the Wnt signaling pathway, as well as VI induced by MGX.…”
supporting
confidence: 52%
“…All these proteins were downregulated, indicating coagulation dysfunction.Signaling pathways are important for VI induced by MGX, as previous research has reported that MGX directly activates the NF-κB signaling pathway via the MAPK pathway (protein accession number: P62987; FC = 5.17)[41]. Our study shows that protein accession number P19474 is a biomarker or drug target, as trim21 upregulation (FC = 1.62) can improve keratinocyte in ammation by activating the NF-κB pathway[49]. According to GO analysis and KEGG pathway annotation and enrichment, our study is the rst to show that the Wnt, ERBB, and BMP signaling pathways are also important for VI induced by MGX; however, the mechanism by which MGX contributes to the pathogenesis of VI through signaling pathways remains unclear.Up-or downregulation of the following proteins (Table2) was closely related to the Wnt signaling pathway, as well as VI induced by MGX.…”
supporting
confidence: 52%
“…IL-6 induces IL-17 to produce an inflammatory response, promotes KC hyperproliferation, and increases T-cell aggregation in the epidermis . IL-17 and TNF-α promote the expression of CCL20 in KCs and further attract dendritic cells as well as Th17 cells, thereby promoting the formation of chemotaxis rings and exacerbating the inflammatory response in psoriasis ( Wang et al, 2015 ; Yang et al, 2020 ). Several in vivo experiments have also indicated that the inhibition of NF-κB activity could significantly improve the inflammatory response in psoriasis ( Kulkarni et al, 2015 ; Irrera et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recent study suggested that TRIM13 interfered TNF receptor associated factor 6 (TRAF6) to upregulate NF-κB activity ( Huang and Baek, 2017 ). TRIM21 has been shown to stimulate NF-κB pathway activation ( Yang et al, 2020 ). Moreover, IκB-α binds p65 subunit, which inhibits NF-κB activation and the IκB proteins are degraded, which promotes p65 entering the nucleus to activate NF-κB ( Scheidereit, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following Salmonella typhimurium infection, TRIM21 is also essential to promote cell death through conferring p62 ubiquitination and proteasomal degradation ( Pan et al, 2016 ; Hos et al, 2020 ). Furthermore, it has been reported that TRIM21 mediates NF-κB activation to aggravate the inflammatory response in psoriasis ( Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%